Sistem Penerangan Jalan Pintar Otomatis-Manual Berbasis Pengabdian Masyarakat untuk Keselamatan Ketenagalistrikan - Tedi Oktavianto Tedi; Usman Nursusanto; Wahyu Prioyono; Sa'adilah Rosyadi; Hartoyo Hartoyo (LPPI UMN AL WASHLIYAH, 2025)
The utilization of electrical energy to support human life activities, especially for lighting at night, is a basic need in urban and rural environments. In rural areas there are still many problems with the lack of lighting at night which has an impact on increasing the risk of accidents and crime. This community service aims to improve environmental safety through the implementation of an automatic-manual system for public street lighting that is reliable, efficient, and in accordance with electricity safety principles. This activity was implemented in the access road of Terbah hamlet, Pengasih, Kulon Progo, Yogyakarta on May 17, 2025 by involving residents in all stages of observation, education, system installation and evaluation. The system is designed using light sensor and Magnetic Contactor for automation, panel box, MCB, Switch, Contact Box, Lamp, and accessories. Implementation methods included electrical safety counseling, hands-on system installation, and the use of modules as technical guides. The evaluation results showed an increase in residents' understanding of safe installation as well as the ability to maintain the lighting system independently. This activity makes a real contribution to the provision of simple sustainable electrical infrastructure and increases awareness of the importance of electricity safety in the community.